K-Pop V Fansubs, V LIVE and NAVER dictionary: Fansubbers’ synergy in minimising language barriers - Aznur Aisyah; Nam, Yun Jin (Penerbit Universiti Kebangsaan Malaysia, 2017)
The translator’s role in delivering K-Pop related content to an international audience has become more important since the expansion of the K-Pop industry throughout the globe. Fans’ anticipation of translated versions of K-Pop videos has led to active subbing activities. The NAVER company in Korea has invented a V Fansubs application for assisting V LIVE video subtitling. V LIVE is a digital media hub that gathers K-Pop celebrity-produced videos on a single platform. The unique tools in V Fansubs and V LIVE applications have made fansubbing of videos, which are mainly delivered in Korean, much easier than before. Netizen communities sharing the same interest have revamped the translation practice by collectively working to provide subtitles using V Fansubs software. This research employed descriptive analysis using Bangtan Sonyeondan’s (BTS) channel in V LIVE as the main sample in explaining V LIVE, V Fansubs and NAVER Dictionary application functions in detail. This research has successfully showcased technical descriptions in modern fansubbing platforms which are scarcely discussed. The linguistic data recorded in these applications have created a mass data corpus linked to the NAVER Dictionary application that is beneficial for Korean language learners. The software is embedded with special functions where phrasal examples extracted from V LIVE and V Fansub contents can be viewed at the same time. The outcome of this research will hopefully shed some light on fansubbing practices that have previously received mixed reactions among scholars.